Effect of polymer charge on functional reconstitution of membrane proteins in polymer nanodiscs. Issue 69 (10th August 2018) - Ravula, Thirupathi; Hardin, Nathaniel Z.; Bai, Jia; Im, Sang-Choul; Waskell, Lucy; Ramamoorthy, Ayyalusamy
Abstract : Although there is growing interest in using polymer lipid-nanodiscs, the polymer charge poses limitations for studies on membrane proteins. Abstract : Although there is a growing interest in using polymer lipid-nanodiscs, the polymer charge poses limitations for studies on membrane proteins. Here, we demonstrate the functional reconstitution of a large soluble-domain containing positively-charged ∼57 kDa cytochrome-P450 and negatively-charged ∼16 kDa cytochrome-b5 in lipid-nanodiscs, and the role of the polymer charge for high-resolution studies on membrane proteins.